Enhancing the Electrocardiogram Signal Quality by Applying Butterworth Infinite Impulse Response Filter 8th Order - Nindia Rena Saputri; Sari Luthfiyah; Dyah Titisari; Bedjo Utomo; Lusiana Lusiana; Triwiyanto Triwiyanto; Faheem Ahmad Reegu; Wahyu Caesarendra (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
The electrocardiogram (ECG) of the human body is an important basis in heart function as well as the diagnosis of cardiovascular diseases, which has a very vital role in clinical diagnosis. Obtaining high-quality ECG signals with a portable remote ECG acquisition system is a big challenge given limited resources. According to the World Health Organization (WHO), disorders of the cardiovascular system still rank high, causing about 31% of deaths globally. This is because the symptoms of cardiovascular disease cannot be seen directly, but rather by conducting an electrocardiograph (ECG) examination. The purpose of this research is to develop and analysis the ECG signal by comparing the 2nd order AD8232 module analogue filter with the 8th order Butterworth digital filter by applying infinite impulse response. This research uses a multiplexer circuit for switching leads, AD8232 ECG module, 50Hz notch filter circuit, non-inverting amplifier, adder, Arduino Mega 2560, USB module, and an application to display digital signals, namely Delphi 7. Signal acquisition is done by monitoring for one minute. Data collection was carried out with 5 respondents 5 times on each lead. The results of the data collection can be concluded that 80% of digital filters display smoother signals for ECG signals than analogue filters.